ANALISIS PERMASALAHAN DAN SOLUSI DALAM PEMBELAJARAN BILANGAN BULAT DI SD NEGERI 060872 - Rizki Fadilah; Elvi Mailani; Septi Utari; Hajjaziah Nasution (Universitas Negeri Medan, 2025)
Learning integers in elementary schools is often a challenge, characterized by students' difficulties in understanding the concept and operating positive and negative numbers. Observational research at SDN 060872 Medan identified crucial problems in this process. This study aims to offer practical and innovative solutions to overcome these obstacles. We propose the implementation of various strategies, including the use of concrete teaching aids, contextual approaches, interactive learning media, and differentiation of teaching methods that are responsive to students' learning styles. The series of solutions offered include visualizing concepts through teaching aids, connecting materials with students' daily experiences, using interactive technology to increase engagement, and adjusting teaching methods to accommodate individual differences. The implementation of these solutions is expected to improve students' conceptual understanding of integers, their ability to solve problems, and create a more inclusive and effective learning environment. This study provides valuable insights for educators and policy makers in improving the quality of mathematics learning at the elementary level.